UV-induced unimolecular photochemistry of 2(5H)-furanone and 2(5H)-thiophenone isolated in low temperature inert matrices - Breda, S. (2008)
Monomers of two simplest five-membered heterocyclic α-carbonyl compounds, 2(5H)-furanone and 2(5H)-thiophenone were isolated in low temperature inert argon matrices and their UV-induced photochemistry was studied. The reaction photoproducts were identified by FTIR spectroscopy and interpretation of the experimental results was assisted by theoretical calculations of the infrared spectra at the DFT(B3LYP)/6-311++G(d,p) level. Both compounds were found to undergo UV-induced α-cleavage photoreaction, however at different excitation wavelengths. The open ring aldehyde-ketene was generated from 2(5H)-furanone upon UV irradiation with λ > 235 nm light, while 2(5H)-thiophenone reacted at lower excitation energies (λ > 285 nm) with formation of thioaldehyde-ketene. At higher excitation energies (λ > 235 nm), thioaldehyde-ketene was transformed into the Dewar isomer and subsequently decomposed with formation of carbonyl sulphide, while aldehyde-ketene did not react any further. The different photochemical reactivity experimentally observed for the two families of compounds was explained on the basis of the natural bond orbital analysis carried out at the MP2/6-311++G(d,p) level of theory.